Resíduos de concreto da construção civil: estudo da viabilidade de fabricação de placas pré-moldadas com vinhaça para potencial utilização em habitações populares - Tamashiro, Jacqueline Roberta (2018)
The process of industrialization, population growth and globalization have led, over the decades, to the increase of industrial activities and intensive and mechanized agriculture, which consequently triggered in disorderly urbanization and increased consumption. These demands have generated until the present day, numerous environmental problems, ranging from the exploratory extraction of natural resources, many of them almost extinct, to the disposal of the residues generated by the manufactured products. This scenario has its aggravating, irregular accumulation of this waste. The construction industry uses non-renewable raw materials in abundance, consuming a large amount of energy in the extraction of inputs, in the production of materials and in the transportation of both. Appropriate treatment and recycling of the generated waste may be the most viable to stop the exploration of degraded areas caused by the disordered extraction. This research aims at the mechanical fabrication and characterization of recycled concrete prototypes and precast concrete panels from Presidente Prudente, and vinasse, a by-product of a sugar and alcohol mills in the Western Region of the State of São Paulo. The methodological process involves the sampling of the recycled concrete aggregate (RCA) and the characterization of the raw material (RCA, cement, sand and gravel) using grain size distribution, grains form, specific mass, water absorption and swelling tests. In sequence, the step manufacturing different traits reproduced in many lots of samples, as well as the physical characterization of the fresh mass by the slump test; setting time of paste (Vicat), pH value and the physical characterization of the test specimens through resistance to mechanical compression strength and mass monitoring. Subsequently, it follows the stage of the manufacture of new test specimens of the trace that presented better results in the previous stage. This trait was physically characterized by porosity; (X-Ray Diffraction (XRD), Fourier Transform Infrared Absorption, Attenuated Total Reflectance (ATR-FTIR)), optical microscopy, Scanning Electron Microscopy (SEM). Finally, the last step involved the fabrication of the prototype of the precast concrete panels and the physical tests (mass monitoring, strength of the surface hardness by the sclerometer and flexural tensile strength in a prismatic prototype). The results indicate the feasibility of use as a constructive material, they also indicate the possibility of minimizing the environmental impacts, by reusing them within the civil construction cycle.